AD biomarker stability for stored CSF based on immunoassay results: Biomarkers (non‐neuroimaging) / Method development and/or quality control. (7th December 2020) - Vandijck, Manu; Bastard, Nathalie Le; Persson, Staffan; Zetterberg, Henrik; Blennow, Kaj; Kostanjevecki, Vesna
Abstract: Background: Diagnosis of Alzheimer's Disease (AD) is currently more often based on a clinical assessment combined with biomarker data. For AD, four core cerebrospinal fluid (CSF) biomarkers have been identified and levels are determined on measurements with various immunoassays (INNOTEST, Lumipulse, Elecsys, etc.). Each assay has its own concept (technology, antibodies, protocol) and performance characteristics. The Alzheimer's Association Quality Control (AA‐QC) program lead by the University of Gothenburg aims to monitor the inter‐laboratory variation for immunoassays for CSF biomarkers using a set of CSF samples (2 round specific & 1 longitudinal), periodically measured at participating sites. Biomarker levels over time of the longitudinal QC CSF sample (2016QC‐L) on the different immunoassays can be interpreted to assess long‐term stability. This is relevant given that CSF samples are often stored in a biorepository as part of a study cohort for future assessment of (new) biomarkers. Method: In the AA‐QC program, immunoassays for the different AD CSF core biomarkers (Aβ1‐42, Aβ1‐40, total‐Tau, and pTau181 ) from different suppliers are tested three times per year with 2016QC‐L. The average result per immunoassay for this sample since round 22 (October 2016) till round 31 (October 2019) were analyzed, considering round 22 as start of storage. Result: For all four CSF biomarkers, the coefficient of variation (CV) per immunoassay obtained over all round averages was below 10% (except one). The CVs ranged from 2% to 10% for Aβ1‐42, 1% to 8% for Aβ1‐40, 1% to 17% for total‐Tau, and 1% to 9% for pTau181, indicating relatively stable concentration assignment over time, despite the use of different batches. For each biomarker, no consistent trend in analyte concentration over all immunoassays in function of time was observed. Conclusion: For the CSF sample analyzed, AD core biomarkers are stable over the follow‐up period of 36 months. The results of the different immunoassays all show a comparable behavior of the analyte concentration over time. These results from Clinical Chemistry practice confirm the long‐term stability of the core CSF biomarkers, lending further support for their use in clinical research studies and therapy monitoring in clinical trials, where stored samples are often analyzed in batch at end‐of‐study.